A Comparison between Radiolabeled Fluorodeoxyglucose Uptake and Hyperpolarized 13C-Labeled Pyruvate Utilization as Methods for Detecting Tumor Response to Treatment - Timothy H. Witney; Mikko I. Kettunen; Samuel E. Day; De-en Hu; Andre A. Neves; Ferdia A. Gallagher; Sandra M. Fulton; Kevin M. Brindle (Neoplasia: An International Journal for Oncology Research, 2009)
Detection of early tumor responses to treatment can give an indication of clinical outcome. Positron emission tomography measurements of the uptake of the glucose analog, [18F] 2-fluoro-2-deoxy-d-glucose (FDG), have demonstrated their potential for detecting early treatment response in the clinic. We have shown recently that 13C magnetic resonance spectroscopy and spectroscopic imaging measurements of the uptake and conversion of hyperpolarized [1-13C]pyruvate into [1-13C]lactate can be used to detect treatment response in a murine lymphoma model. The present study compares these magnetic resonance measurements with changes in FDG uptake after chemotherapy. A decrease in FDG uptake was found to precede the decrease in flux of hyperpolarized 13C label between pyruvate and lactate, both in tumor cells in vitro and in tumors in vivo. However, the magnitude of the decrease in FDG uptake and the decrease in pyruvate to lactate flux was comparable at 24 hours after drug treatment. In cells, the decrease in FDG uptake was shown to correlate with changes in plasma membrane expression of the facilitative glucose transporters, whereas the decrease in pyruvate to lactate flux could be explained by an increase in poly(ADP-ribose) polymerase activity and subsequent depletion of the NAD(H) pool. These results show that measurement of flux between pyruvate and lactate may be an alternative to FDG-positron emission tomography for imaging tumor treatment response in the clinic.